2014
DOI: 10.3109/01460862.2014.951131
|View full text |Cite
|
Sign up to set email alerts
|

Maternal concerns about immunization over 0–24 month children: a qualitative research

Abstract: The purpose of this qualitative study was to determine the concerns of mothers referred to health center in south Tehran, Iran about immunizing children aged 0-24 months. Data were collected using individual semi-structured interviews and analyzed using content analysis. The mothers' concerns over immunizing their children fell into 5 main categories: (1) "Factors that cause mothers' concerns," (2) "Factors that influence mothers' concerns," (3) "Information, education, and communication barriers," (4) "Inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(50 citation statements)
references
References 21 publications
2
48
0
Order By: Relevance
“…Many studies attested to the important role of health workers in providing vaccination information to parents (Berhanel 2000; Guillaume 2004; McMurray 2004; Benin 2006; Hilton 2007; Tickner 2007; Gust 2008; Miller 2008; Tadesse 2009; Austvoll-Dahlgren 2010; Tickner 2010; Bond 2011; Brunson 2013; Brown 2014; Delkhosh 2014; Fadda 2015; Harmsen 2015; Kowal 2015; Saada 2015; Dube 2016; Sobo 2016). For parents who accepted vaccination, these health workers worked within the allopathic health system and were public health nurses, paediatricians, general practitioners and general health workers (Guillaume 2004; McMurray 2004; Benin 2006; Tickner 2007; Gust 2008; Miller 2008; Tadesse 2009; Austvoll-Dahlgren 2010; Brunson 2013; Delkhosh 2014; Fadda 2015; Harmsen 2015; Kowal 2015; Saada 2015; Dube 2016; Sobo 2016).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Many studies attested to the important role of health workers in providing vaccination information to parents (Berhanel 2000; Guillaume 2004; McMurray 2004; Benin 2006; Hilton 2007; Tickner 2007; Gust 2008; Miller 2008; Tadesse 2009; Austvoll-Dahlgren 2010; Tickner 2010; Bond 2011; Brunson 2013; Brown 2014; Delkhosh 2014; Fadda 2015; Harmsen 2015; Kowal 2015; Saada 2015; Dube 2016; Sobo 2016). For parents who accepted vaccination, these health workers worked within the allopathic health system and were public health nurses, paediatricians, general practitioners and general health workers (Guillaume 2004; McMurray 2004; Benin 2006; Tickner 2007; Gust 2008; Miller 2008; Tadesse 2009; Austvoll-Dahlgren 2010; Brunson 2013; Delkhosh 2014; Fadda 2015; Harmsen 2015; Kowal 2015; Saada 2015; Dube 2016; Sobo 2016).…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies discussed parents' expectations of health workers in relation to communicating information about vaccination (Bond 1998; Berhanel 2000; Evans 2001; Guillaume 2004; McMurray 2004; Shui 2005; Benin 2006; Fowler 2007; Tickner 2007; Austin 2008; Gust 2008; Henderson 2008; Miller 2008; Tadesse 2009; Austvoll-Dahlgren 2010; Tickner 2010; Bond 2011; Brown 2012; Harmsen 2012; Hussain 2012; Brown 2014; Delkhosh 2014; Brunson 2015; Fadda 2015; Harmsen 2015; Kowal 2015; Saada 2015; Dube 2016; Sobo 2016). The studies suggested that many parents expected:…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations